Changes and challenges for behavioral – cognitive therapy starting with covid-19: reflections on telepsychotherapy - Chirio-Aldazabal, Diego (2023)
Since the beginning of 2020, different countries have been adopting confinement and protection measures against the infection caused by Sars-Cov-2, which represented a challenge for health professionals, in the case of psychology, the therapies provided in face-to-face modality were interrupted, becoming carried out online. Three years after these events, it is worth reflecting on what the use of telepsychotherapy implied as a modality supported by evidence under certain criteria to promote its therapeutic effects. Based on this, we begin to reflect on what the covid-19 context implied in psychology, more specifically in the clinical area, generating greater notoriety of psychological/psychiatric disorders in the general population. From this, it is convenient to approach telepsychotherapy in two blocks, the first referring to the growing evidence on the therapeutic effectsachieved, which position it as a supported alternative; while, in parallel, the bases that support its potential effects are considered at all times. It ends by mentioning the limitations that could be found in this form of intervention.